Rethinking Fistula Preservation in Anorectal Malformation Surgery: A Histopathological Perspective - Agarwal, Preeti; Roy, Shubhajeet; Pandey, Anand; Tyagi, Nirpex; Pant, Nitin; Kumar, Piyush; Rawat, Jiledar (European Journal of Pediatric Surgery, 2024)
Objective This study aims to assess the histopathological characteristics of the fistulous tissue in males with anorectal malformation (ARM) to determine its suitability for use in constructing a neoanus.Methods This prospective observational study included male ARM patients with recto-urethral fistula. All other types were excluded. The tissue specimens comprised 0.5 to 2.0 cm of the most distal part of the rectal pouch and the fistulous tissue. Hematoxylin and eosin-stained sections were prepared. Histological features, viz. internal sphincter, anal grand and crypts, ganglion cells, presence of subepithelial fibrosis, thickened nerve trunks, and metaplasia, were evaluated.Results Of 65 patients of ARM admitted, 24 met the inclusion criteria. Gross and microscopic internal sphincter was not found in any sample. The anal mucosa was visualized in all samples; however, crypts were irregular and distorted architecture was seen in 4 (16.67%) samples. Urothelial metaplasia was identified in 10 (41.67%) samples. Adequate ganglion cells were seen only in 6 (25%) samples. Significant submucosal fibrosis was seen in all samples. Thickened nerve trunks were identified in 4 (16.67%) samples.Conclusions All normal anal histological features could not be found together in the fistula tissue. With the absence of normal features, such as internal anal sphincter muscles, and the presence of abnormal histopathological features, such as subepithelial fibrosis, thickened nerve trunks, and metaplasia, there are high chances of abnormal bowel function like constipation if the fistulous tissue is used for neoanus construction. It may have an impact on the quality of life of patients.
Keywords: anorectal malformation; fistula; histopathology; PSARP; surgery